A novel composite inorganic retarding gel for preventing coal spontaneous combustion. (December 2021) - Cheng, Jianwei; Wu, Yuhang; Dong, Ziwen; Zhang, Rui; Wang, Wenbin; Wei, Guoying; Chu, Tingxiang; Yu, Zhaoyang; Qin, Yi; Liu, Guozhong; Li, Haijian
Abstract: In order to better control the fire problem due to coal oxidations, a novel composite inorganic retarding gel material processed from sodium-based bentonite junction and kaolin, silica, hydrogen peroxide and silicon oxide is developed. For studying the gel's properties the scanning electron microscopy (SEM) and the thermogravimetry (TG-DTG) are used to characterize microscopical structures and mass losses with the temperature change process, respectively. For quantifying the inhibitory effect of the novel gel on the spontaneous combustion process of coal oxidation, laboratory tests such as temperature-programmed oxidation and infrared spectroscopy are carried out. Changes of the gases generated from the treated coal sample by the novel gel under the temperature increasing are analyzed. The inhibitory effects of mud and MgCl2 solutions on coal spontaneous combustion are compared. The results show that the surface of the gel is flat and smooth in microscopic scale. Under the a high-temperature, the gel is stable and is not easy to decompose. In detail, the quality loss is within 10%. The novel gel with a concentration of 20% has a good inhibitory effect on CO release and spontaneous combustion in coal combustion. In addition, the novel gel can significantly reduce the consumption of –OH, –CH and other functional groups in the low-temperature oxidation reaction. Hence, the novel gel is a kind of Inhibitor material with a better comprehension performance. This study provides a novel gel for better preventing and controlling the coal spontaneous combustion hazard.